Assessing Sedimentary Boundary Layer Calcium Carbonate Precipitation and Dissolution Using the Calcium Isotopic Composition of Pore Fluids - James, Daniel H.; Bradbury, Harold J.; Antler, Gilad; Steiner, Zvi; Hutchings, Alec M.; Sun, Xiaole; Saar, Raoul; Greaves, Mervyn; Turchyn, Alexandra V. (Frontiers in Earth Science, 2021)
We present pore fluid geochemistry, including major ion and trace metal concentrations and the isotopic composition of pore fluid calcium and sulfate, from the uppermost metre of sediments from the Gulf of Aqaba (northeast Red Sea) and the Iberian Margin (North Atlantic Ocean). In both locations, we observe strong correlations between calcium, magnesium, strontium and sulfate concentrations as well as the sulfur isotopic composition of sulfate and alkalinity, suggestive of active changes in redox state and pH that should lead to carbonate mineral precipitation and dissolution. The calcium isotope composition of pore fluid calcium (44Ca) is, however, relatively invariant in our measured profiles, suggesting that carbonate mineral precipitation is not occurring within the boundary layer at these sites. We explore several reasons why the pore fluid 44Ca might not be changing in the studied profiles, in spite of changes in other major ions and their isotopic composition, including mixing between the surface and deep precipitation of carbonate minerals below the boundary layer, the role of active iron and manganese cycling in inhibiting carbonate mineral precipitation and that mineral precipitation may be slow enough to preclude calcium isotope fractionation during carbonate mineral precipitation. Our results suggest that active carbonate dissolution and precipitation, particularly in the diffusive boundary layer, may elicit a more complex response in pore fluid 44Ca than previously thought.